Prospek Usaha Simplisia Kunyit (Curcuma domestica Val.) di Bali Ditinjau dari Analisis Finansial - Mahagiri, I Made Teguh; Mulyani, Sri; Satriawan, Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 1 (2021): Maret, 2021)
Analysis of the financial aspects is a crucial thing in planning a business to determine the feasibility of the business. The research aims to: evaluating by financial the business of turmeric simplicia and determine the investment value of the business of turmeric simplicia. First, this study began with the identification and observation of problems to collects the datas then we have financial analysed with 5 criterias, there are Net Present Value (NPV), Net Benefit-Cost Ratio (Net B / C), Internal Rate of Return (IRR), Profitability (PR) and Payback Period (PP). The results showed that turmeric simplicia business is feasible to run with a Net Present Value result is Rp. 80.792.466 and Internal Rate of return is 13% and Payback Period for 1,95 years and B/C Ratio 1,22 with Profitability 2,16. Sensitivity tests show decreased and increased income of 2% and 3%, it means the business is still feasible. The investment for turmeric is Rp. 206.072.626 which from own capital is Rp. 164.858.101 and loans of Rp. 41.214.525. Keywords : turmeric, simplicia, financial analysis